Computational Mathematics and Applied Statistics - Ferreira, Sandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Rapid advances in modelling research have created new challenges and opportunities for statisticians. Statistical inference in observational studies and many other emerging fields have motivated statisticians worldwide to develop cutting-edge methods and analytical strategies. The aim of this reprint is to showcase the applications and methodological research in all fields of computational statistics. This reprint will provide a forum for computer scientists, mathematicians, and statisticians working in a variety of areas in statistics, including biometrics, econometrics, data analysis, graphics, and simulation.